PENGARUH MOTIVASI DAN KEPUASAN KERJA TERHADAP KINERJA GURU DIMEDIASI DENGAN KOMITMEN ORGANISASIONA ( Studi pada guru SD Negeri di UPTD Pendidikan Kecamatan Genuk Semarang) (Students' Journal of Economic and Management, 2012)
This research is aimed to test and analyze the influence of motivation and job satisfactory towards teacher’s working mediated with organizational commitment of the teacher of  s State Elementary School in “ UPTD Kecamatan Genuk Semarang”, with 146 respondences. The technique of collecting data used is random samplimh by giving a austioner to the respondences. This research is aimed    to: 1)Analyze the influence of motivation towards organisational commitment , 2) Analyze  the job satisfactory towards organizational commitment, 3) Analyze the influence of motivation towards teacher’s working, 4) Analyze the influence of satisfactory towards  teacher’s working, 5) Analyze the influence of organizational commitment towards teacher’s working, 6) Analyze and prove the organizational commitment as an influence of motivation ‘ mediation towards  teacher’s working, 7) Analyze and prove organisational commitment as an influence of working satisfactory’s mediation towards teacher’s working. The technique of testing data which is used in this research includes validity with factor analysis and reliability testbyCronbach's alpha formula, multiple regression analysis, tests of significance and coefficient of determinationto prove thetruth ofthe hypothesisof the study,as well astestingthe effect ofmediation. The result of the research showed that: 1). Motivation didn’t influence positively towards organizational commitment, 2). Job satisfactory influences positively and significantly towards organizational commitment, 3). Motivation influences positively and cantly towards teacher’s working, 4).Job satisfactory didn’t influencedirectly towarde teacher’s working, 5)OrganizationalCommitment influence positive andsignificanteffecton the performance ofteachers witha positivebetaand significancepricesbelowarerequired. 6)organizationalcommitmentdid notmediate theeffect ofwork motivation, whilework motivationdirectly affects theperformance of teachers. 7)Organizationalcommitmentmediates theinfluence ofjob satisfactory towards teacher’s working. Keywords: Motivation, Job Satisfactory, OrganizationalCommitmenta  working